2014
DOI: 10.3389/fnbeh.2014.00326
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of olfactory sensitivity and glucose-sensing by the feeding state in obese Zucker rats

Abstract: The Zucker fa/fa rat has been widely used as an animal model to study obesity, since it recapitulates most of its behavioral and metabolic dysfunctions, such as hyperphagia, hyperglycemia and insulin resistance. Although it is well established that olfaction is under nutritional and hormonal influences, little is known about the impact of metabolic dysfunctions on olfactory performances and glucose-sensing in the olfactory system of the obese Zucker rat. In the present study, using a behavioral paradigm based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 107 publications
1
20
0
2
Order By: Relevance
“…Thus, GLUT4, in addition to peptides involved in food intake regulation, could be responsible for the difference in olfactory sensitivity observed between satiated and fasted rats (Aimé et al, 2007 ). This hypothesis schematized in Figure 7 , is consistent with a recent study showing that impairment of GLUT function could alter olfactory sensitivity in obese fa/fa rats compared to their lean counterparts (Aimé et al, 2014 ). Concerning SGLT1, we suggest that this glucose sensing marker could be involved in maintaining local energy reserves to support bulbar synaptic function known to require very high budget of energy (Nawroth et al, 2007 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, GLUT4, in addition to peptides involved in food intake regulation, could be responsible for the difference in olfactory sensitivity observed between satiated and fasted rats (Aimé et al, 2007 ). This hypothesis schematized in Figure 7 , is consistent with a recent study showing that impairment of GLUT function could alter olfactory sensitivity in obese fa/fa rats compared to their lean counterparts (Aimé et al, 2014 ). Concerning SGLT1, we suggest that this glucose sensing marker could be involved in maintaining local energy reserves to support bulbar synaptic function known to require very high budget of energy (Nawroth et al, 2007 ).…”
Section: Discussionsupporting
confidence: 90%
“…The modulation of this glucose sensor expression in the OB seems to be restricted to pathological contexts such as obesity. Indeed, we have recently demonstrated an up-regulation of SGLT1 in the OB of insulin-resistant and obese Zucker fa/fa rats (Aimé et al, 2014 ). In various pathological contexts like obesity, epilepsy or ischemia (Poppe et al, 1997 ; Elfeber et al, 2004 ; Aimé et al, 2014 ) up-regulation of SGLT1 in specific brain areas is essential to compensate impairment in GLUTs function and to preserve glucose-sensing function (Poppe et al, 1997 ; Elfeber et al, 2004 ; Yu et al, 2010 , 2013 ; Aimé et al, 2014 ).…”
Section: Discussionmentioning
confidence: 92%
“…Our current data demonstrate no change in odorant discrimination or threshold when insulin is administered in a daily regimen. It is well known that insulin modulates mitral cell (MC) firing frequency when applied acutely [20, 51, 52] as a driver of state-dependent odor processing that could affect olfactory ability during fasting or satiety states [16, 20, 53, 54]. During the postprandial period of insulin release, untreated animals would be expected to respond to such insulin fluctuations, whereas our chronic insulin IND-treated animals with already elevated plasma insulin levels would be predicted to not electrically detect a new insulin baseline by exhibiting altered MC activity.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT4 and IR are found to be localized in the main central olfactory areas such as the OB, PC, anterior olfactory nucleus (AON), and olfactory tubercle (OT) (Unger et al, 1989; Marks et al, 1990; El Messari et al, 1998; Schulingkamp et al, 2000; Alquier et al, 2006; Aimé et al, 2012, 2014). In a previous study, we have shown that GLUT4 is co-localized with IR in MCs and glomeruli of the OB.…”
Section: Glucose Sensingmentioning
confidence: 99%